Pendampingan Penerapan Sistem Informasi pada Pos Kesehatan Paroki Keluarga Kudus Yogyakarta - Kristian Adi Nugraha; Danny Sebastian; Maria Nila Anggia Rini (Patria : Jurnal Pengabdian Kepada Masyarakat, 2020)
Paroki Keluarga Kudus Yogyakarta want to implementing information technology system on its medical service activity because its administration process was not effective and efficient at all. But the problem is they didn't have any human resources that capable to implementing information technology system. So, they ask Fakultas Teknologi Informasi Universitas Kristen Duta Wacana to accompany them for implementing information technology on their medical service activity.